The Effect of Organizational Culture on Business Strategy Development: A Qualitative Study on Creative Industries - Labib, Muhammad (Siber International Journal of Digital Business (SIJDB), 2024)
This research examines the influence of organizational culture on business strategy development and implementation in the creative industries in West Java, Indonesia. Through a qualitative approach, this study collected data from 15 creative companies in West Java, using in-depth interview techniques, participatory observation, and document analysis. Data analysis was conducted using content and thematic analysis methods to identify how organizational culture values, such as collaboration, adaptability, innovation, employee engagement, and customer orientation, influence business strategy development and implementation. The results show that an organizational culture that encourages collaboration and adaptability enhances the company's ability to innovate and be responsive to market changes. In addition, cultures that support employee engagement and focus on customer satisfaction prove vital in improving the effectiveness of business strategies. These findings underscore the importance of building and maintaining a positive organizational culture as a strategic asset in a dynamic business environment. This study contributes to the strategic management literature by highlighting how organizational culture can serve as a driving force in achieving strategic success in the creative industry. Suggestions for practitioners and future research directions are also discussed.